Anomalous behavior of localized magnetic centers in (Sm,Er)123 compound - Guskos, N.; V. Likodimos; Wabia, M.; Typek, J.; Grybos, J.; Fuks, H. (Physica B: Condensed Matter, 2000)
The EPR spectrum of the oxygen-deficient Sm0.5Er0.5Ba2Cu3O6+x mixed phase has been investigated in the temperature range of 3.3-20 K. Anomalous behavior of the EPR spectrum has been detected below 4 K that may indicate the presence of magnetic centers with singlet ground state and an excitation energy of the order of 1 K. © 2000 Elsevier Science B.V. All rights reserved.